UASB reactor in residual wastewater treatment - dairy industry - Martins, Ramiro (2016)
The discharge of wastewater into water bodies is still quite common in developing countries, such as the case of Angola. The application of the UASB reactor - Upflow Anaerobic Sludge Blanket process is presented as a viable alternative to be used, given the characteristics of the domestic / industrial wastewater to be treated and local economic needs. Thus, this study was developed with an anaerobic treatment technology using an UASB reactor, analysing its effectiveness in relation to the removal of organic matter and solids, evaluating the application of different volumetric organic loads under conditions similar to the real ones, in a laboratory pilot plant. The UASB reactor shaping a “Y” was constructed with PVC and a useful volume of 12 litres; it was designed to operate at steady state at a temperature around 35ºC. The most promising results showed COD removal efficiencies of approximately 76%, BOD 79% and TSS 88%.